Vibro-acoustic analysis of coupled tyre model of acoustic cavity and tread structure. (2017) - Ebrahimi-Nejad, Salman; Karimyan, Amir
A coupled model of tyre tread band and acoustic cavity is presented in this paper. Modal and harmonic analyses show that this simplified coupled structure can resemble the noise characteristics of the tyre with great accuracy. Then, we use the coupled model to study the impact of effective structural and fluid properties on acoustic pressure and sound pressure level, as well as tyre tread deformations. Results indicate that the use of helium and hydrogen moves the first resonant frequency to above 250 Hz and displaces the second peak to above 400 Hz, and hydrogen leads to more than 3 dB decrease in sound pressure level.